Tumor Microenvironment Targeted Nanotherapy - Fernandes, Clara; Suares, Divya; Yergeri, Mayur C (Frontiers in Pharmacology, 2018)
Recent developments in nanotechnology have brought new approaches to cancer diagnosis and therapy. While enhanced permeability and retention effect (EPR) promotes nanoparticle (NP) extravasation, the abnormal tumor vasculature, high interstitial pressure and dense stroma structure limit homogeneous intratumoral distribution of NP and compromise their imaging and therapeutic effect. Moreover, heterogeneous distribution of NP in nontumor-stroma cells damages the nontumor cells, and interferes with tumor-stroma crosstalk. This can lead to inhibition of tumor progression, but can also paradoxically induce acquired resistance and facilitate tumor cell proliferation and metastasis. Overall, the tumor microenvironment plays a crucial, yet controversial role in regulating NP distribution and their biological effects. In this review, we summarize the barriers in tumor microenvironment and discuss the consequential effects of NP considerations to improve NP delivery and propose potential combinatory strategies to overcome acquired resistance induced by tumor microenvironment. The various strategies that have been adopted have been discussed in this review article.